Admission and discharge decisions in emergency medicine (Hanley & Belfus, 2002)
(Hanley & Belfus) Univ. of Washington, Seattle. Gives emergency physicians objective data on which to base admission decisions. Includes most common clinical problems as well as diagnoses with research and clinical consensus guidelines on whom to admit. Examines current standard of care and looks at new ideas pertaining to the admission decision.